Septal reduction therapies in hypertrophic cardiomyopathy: comparison of surgical septal myectomy and alcohol septal ablation. (April 2014) - Geske, Jeffrey B; Klarich, Kyle W; Ommen, Steve R; Schaff, Hartzell V; Nishimura, Rick A
Abstract Left ventricular outflow tract obstruction, either resting or labile, occurs in approximately 70% of patients with hypertrophic cardiomyopathy and is a major cause of symptoms. In patients with obstructive physiology and medically refractory symptoms, septal myectomy and alcohol septal ablation reduce the left ventricular outflow tract gradient and improve symptoms. Myectomy is more effective at gradient reduction compared with ablation, with lower need for subsequent pacemaker implantation. However, cohort studies and meta-analyses have shown short-term mortality and post-procedural functional classes are similar between procedures. In many centers alcohol septal ablation case volumes have surpassed myectomy. There remains significant controversy regarding choice of myectomy or ablation. This review describes the two septal reduction procedures, examines the available comparative data for clinical outcomes and discusses clinical considerations when selecting myectomy or ablation.